Silica particles and method for producing same, silica sol, polishing composition, polishing method, method for producing semiconductor wafer, and method for producing semiconductor device
By optimizing the nano-scale pore structure of silica particles and reducing alkoxy residues, the problems of insufficient mechanical strength, abrasive characteristics and storage stability of existing silica particles are solved, and higher mechanical strength and better abrasive performance are achieved.
Patent Information
- Application Number
- CN202380048348.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-20
- Filing Date
- 2023-06-16
- Publication Date
- 2025-03-07
AI Technical Summary
The existing silica particles are insufficient in mechanical strength, grinding characteristics and storage stability, which leads to easy damage during the grinding process, affecting the grinding efficiency and product quality.
By optimizing the nano-scale pore structure of silica particles, ensure that the average pore volume of the nano-scale pores is below 5.3 nm3, reducing pores to become the starting point for breaking, and reducing alkoxy residues inside the particles, thereby improving mechanical strength and storage stability.
It improves the mechanical strength, grinding characteristics and storage stability of silica particles, reduces particle damage during the grinding process, and improves grinding efficiency and product quality.
Smart Images

Figure BDA0005197632710000061 
Figure BDA0005197632710000062 
Figure BDA0005197632710000071
Abstract
Description
Technical Field
[0001] The present invention relates to silicon dioxide particles and a method for producing the same, a silica sol, an abrasive composition, a polishing method, a method for producing a semiconductor wafer, and a method for producing a semiconductor device. Background Art
[0002] As a method for polishing the surface of materials such as metals and inorganic compounds, polishing methods using polishing liquids are known. Among them, in chemical mechanical polishing (CMP) such as final fine polishing of prime silicon wafers and regenerated silicon wafers for semiconductors, planarization of interlayer insulating films, formation of metal plugs, and formation of embedded wiring during semiconductor device manufacturing, the surface state has a great influence on semiconductor characteristics, so the surfaces and end faces of these components are required to be polished with extremely high precision.
[0003] In such precision grinding, a polishing composition containing silica particles is used, and colloidal silica is widely used as the abrasive grain as the main component. Colloidal silica is known to be colloidal silica obtained by thermal decomposition of silicon tetrachloride (fumed silica, etc.), colloidal silica obtained by deionization of alkali metal silicates such as water glass, and colloidal silica obtained by hydrolysis and condensation reaction of alkoxysilane (generally referred to as "sol-gel method"), depending on the production method.
[0004] Many studies have been conducted so far on methods for producing silica particles. For example, Patent Documents 1 and 2 disclose methods for producing silica particles by hydrolysis and condensation reactions of alkoxysilane.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Laid-Open No. 11-60232
[0008] Patent Document 2: Japanese Patent Application Publication No. 2019-89692 Summary of the invention
[0009] Problem that the invention aims to solve
[0010] Furthermore, generally speaking, it is impossible to say that the mechanical strength of the silica particles obtained by the hydrolysis reaction and condensation reaction of alkoxysilane is high enough. Moreover, if the silica particles with insufficient mechanical strength are used for grinding, the silica particles are destroyed during grinding, and the destroyed silica particles adhere to the ground body, etc., producing adverse effects during grinding. In addition, if the silica particles are destroyed during grinding, sufficient grinding rate cannot be maintained. Moreover, the storage stability of such silica particles is poor.
[0011] The silica particles obtained by the production methods disclosed in Patent Documents 1 and 2 are inferior in mechanical strength, polishing properties, and storage stability.
[0012] The present invention is accomplished in view of such problems, and an object of the present invention is to provide silicon dioxide particles, silica sol, and abrasive compositions having excellent mechanical strength, polishing properties, and storage stability. In addition, another object of the present invention is to provide a polishing method having excellent productivity of a polished body, a method for manufacturing a semiconductor wafer, and a method for manufacturing a semiconductor device.
[0013] Methods used to solve problems
[0014] The mechanical strength, grinding characteristics and storage stability of the previous silica particles may not be sufficient. The inventors of the present invention focus on the crushing of silica particles as the reason for reducing the mechanical strength, grinding characteristics and storage stability of silica particles, and have repeatedly carried out in-depth research on reducing the crushing of the silica particles. As a result, the inventors of the present invention have found that there are nanoscale pores inside the silica particles, and found that when the nanoscale pores are large, the nanoscale pores become the starting point of crushing, so the mechanical strength is reduced. In addition, the inventors of the present invention have found that the silica particles with large nanoscale pores have a large amount of residual alkoxy groups inside the particles, so the alkoxy groups react during storage, etc., and the storage stability is poor. Furthermore, the inventors of the present invention have found that by optimizing the nanoscale pores measured by the positron annihilation method, the pores of the silica particles can be suppressed from becoming the starting point of crushing, and the mechanical strength, grinding characteristics and storage stability of the silica particles are improved, thereby completing the present invention.
[0015] That is, the gist of the present invention is as follows. [1]
[0017] A silica particle, wherein the average pore volume of nanoscale pores measured by positron annihilation method is 5.3 nm 3 the following. [2]
[0019] The silica particles according to [1], wherein the average pore volume of nanoscale pores measured by positron annihilation method is 4.0 nm 3 the following. [3]
[0021] The silica particles according to [1], wherein the average pore volume of nanoscale pores measured by positron annihilation is 1.5 nm 3 above. [4]
[0023] The silica particles according to [1], wherein the average pore volume of atomic-scale pores measured by positron annihilation is 0.33 nm 3 above. [5]
[0025] The silica particles according to [1], wherein the average pore volume of atomic-scale pores measured by positron annihilation is 0.80 nm 3 the following. [6]
[0027] The silica particles according to [1], wherein the volume of pores having a diameter of 2 nm or less measured by a nitrogen adsorption method is 0.0070 cm 3 / g or less. [7]
[0029] The silica particles according to [1], wherein the refractive index is 1.390 or more. [8]
[0031] The silica particles according to [1], wherein the metal impurity content is 5 ppm or less. [9]
[0033] The silica particles according to [1], wherein the main component is a tetraalkoxysilane condensate.
[10]
[0035] A method for producing silica particles is the method for producing silica particles according to any one of [1] to [9], comprising the step of performing a hydrolysis reaction and a condensation reaction of alkoxysilane at 40° C. or higher.
[11]
[0037] A silica sol comprising the silica particles according to any one of [1] to [9].
[12]
[0039] A polishing composition comprising the silica sol described in
[11] .
[13]
[0041] A grinding method comprising grinding using the grinding composition described in
[12] .
[14]
[0043] A method for producing a semiconductor wafer, comprising: a step of polishing using the polishing composition described in
[12] .
[15]
[0045] A method for manufacturing a semiconductor device, comprising: a step of polishing using the polishing composition described in
[12] .
[0046] Effects of the Invention
[0047] The silica particles of the present invention have improved mechanical strength, polishing properties, and storage stability. The silica particles of the present invention are not easily broken in the step of polishing an object to be polished using a polishing composition containing the silica particles.
[0048] Therefore, by using the silica sol and polishing composition containing the silica particles of the present invention, the polishing object can be effectively polished without damaging it, and the silica particles can be easily removed after polishing. Therefore, high-quality polishing products can be manufactured with good productivity. DETAILED DESCRIPTION
[0049] The present invention is described in detail below, but the present invention is not limited to the following embodiments and can be implemented with various modifications within the scope of its purpose. It should be noted that when the expression "to" is used in this specification, it is used as an expression including the numerical value or physical property value before and after it.
[0050] (Silicon dioxide particles)
[0051] The average pore volume of nanoscale pores measured by positron annihilation method (hereinafter also referred to as "average pore volume of nanoscale pores") of the silica particles of the present invention is 5.3 nm. 3 Below, preferably 4.0nm 3 Below, more preferably 3.5 nm 3 As a result, the starting point of fracture of the silica particles is reduced, and the mechanical strength, polishing properties, and storage stability of the silica particles can be improved.
[0052] The reason for forming the nanometer-scale pores of silica particles can be considered to be that the reaction speed of the hydrolysis reaction and condensation reaction of alkoxysilane is not fast enough, and the particle growth is carried out before the four bonding bonds of the silicon atom form the siloxane bond, and the alkoxy group and the silanol group remain inside the particle. The pores of the silica particles with large nanometer-scale pores become the starting point of crushing, so the mechanical strength is poor. If such silica particles with large nanometer-scale pores are used for grinding, the silica particles are destroyed in grinding, and the destroyed silica particles are attached to the ground body, etc., and adverse effects are produced in grinding. In addition, if the silica particles are destroyed in grinding, sufficient grinding rates cannot be maintained. Moreover, the silica particles with large nanometer-scale pores have a large amount of residual alkoxy groups inside the particles, so the alkoxy groups react during storage, etc., and the storage stability is poor.
[0053] The silica particles of the present invention have an average pore volume of nano-sized pores within the above range, which reduces the starting point of fracture of the silica particles and reduces the number of alkoxy groups remaining inside the particles. This is believed to improve the mechanical strength, polishing properties, and storage stability of the silica particles.
[0054] The lower limit of the average pore volume of the nanoscale pores of the silica particles is not particularly limited, but is preferably 1.5 nm from the viewpoint of maintaining the flexibility of the particles and preventing damage during polishing. 3 More preferably 2.0 nm 3 More preferably, 2.5 nm 3 above.
[0055] The positron annihilation method is a method for measuring the lifetime of a positron by the time difference between the moment a positron is emitted and the moment a gamma ray generated when the positron is annihilated is observed. When a positron is injected into a material, the larger the vacancy defect in the material, the longer the lifetime of the positron. Using this property, the average pore volume of the nanoscale pores of silica particles and the average pore volume of the atomic-scale pores described later can be measured.
[0056] The average pore volume of the nanoscale pores of the silica particles in this specification refers to the value measured by the positron annihilation method. Specifically, the positron lifetime spectrum obtained by applying the positron annihilation method to the dried silica particles is fitted with the linear sum of four exponential functions to find the average lifetime of the positrons of each component. Among the four exponential function components, the two components with short lifetimes are components that are unrelated to the material. The component with the third shortest lifetime is equivalent to the atomic-level pores described later. The component with the fourth shortest lifetime is a component equivalent to the nanoscale pores. Substituting its average lifetime into the following formula, it is converted into the volume of the pores, thereby obtaining the average pore volume. According to the obtained average pore volume of the nanoscale pores of the silica particles, it is possible to grasp the pores surrounded by Si-O-Si structures, silanol groups and / or alkoxy groups, etc., mainly those larger than 1nm in the silica particles. 3 The volume of the pores.
[0057] It should be noted that the relationship between the positron lifetime and the pore volume is based on K. Wada et al., J. Phys.: Conf. Ser. 443, 012003 (2013).
[0058] [Formula 1]
[0059]
[0060] in,
[0061] [Formula 2]
[0062]
[0063] τ is the average lifetime of positrons, R is the average radius of nanopores, r0 is the correction value of the radius of nanopores, and λ T is the annihilation rate of normal positronium in vacuum, and V is the average pore volume of nanoscale pores.
[0064] As a method for measuring pore volume, there are other methods that use gas adsorption and desorption, such as nitrogen adsorption method, but gas adsorption and desorption method has the following problems: it cannot measure closed pores, and the measurement results will be erroneous due to the chemical interaction between the measured object and the detection gas. The positron annihilation method can also measure the volume of closed pores, and it does not rely on the chemical characteristics of the measured object, so it can be measured with high accuracy.
[0065] From the viewpoint of further improving the mechanical strength, polishing properties and storage stability of the silica particles, the average pore volume of the atomic-level pores of the silica particles measured by positron annihilation method (hereinafter also referred to as “the average pore volume of the atomic-level pores”) is preferably 0.33 nm. 3 More preferably 0.35 nm 3 More preferably, 0.37 nm 3 In addition, from the viewpoint of maintaining the stability of the bond angle of the siloxane bond, the average pore volume of the atomic-scale pores is preferably 0.80 nm. 3 Below, more preferably 0.60nm 3 Below, more preferably 0.45 nm 3 the following.
[0066] The average pore volume of atomic-scale pores of silica particles in this specification refers to the value measured by positron annihilation method. The positron lifetime spectrum is obtained by the same method as the determination of the average pore volume of nanoscale pores, and the four components are fitted. The average lifetime of the third shortest component is substituted into the following formula, converted into the volume of pores, and the average pore volume of atomic-scale pores is obtained. Based on the obtained average pore volume of atomic-scale pores of silica particles, the volume of pores inside the ring structure of the siloxane network, mainly the 1 nm in the silica particles, can be grasped. 3 The volume of the pores below the volume.
[0067] [Formula 3]
[0068]
[0069] in,
[0070] [Formula 4]
[0071]
[0072] τ is the average lifetime of positrons, R is the average radius of atomic pores, ΔR is the correction value of the radius of atomic pores, and V is the average pore volume of atomic pores.
[0073] The mechanical strength of silica particles can be adjusted by the pore volume. From this point of view, the volume of pores with a diameter of 2 nm or less measured by nitrogen adsorption is preferably 0.0070 cm 3 / g or less, more preferably 0.0060cm 3 / g or less, more preferably 0.0050cm 3 In addition, from the viewpoint of maintaining the flexibility of the structure of the silica particles, the volume of pores with a diameter of 2 nm or less measured by a nitrogen adsorption method is preferably 0.0005 cm 3 / g or more, more preferably 0.001cm 3 / g or more, more preferably 0.0015cm 3 / g or above.
[0074] When the refractive index of the silica particles is large, the atomic density of the silica particles is high and the mechanical strength is easily maintained, so the refractive index is preferably 1.390 or more, more preferably 1.400 or more, and further preferably 1.410 or more. In addition, the silica preferably maintains an amorphous structure, so the refractive index is preferably 1.550 or less, more preferably 1.500 or less, and further preferably 1.450 or less.
[0075] The refractive index of the silica particles was determined by adding special grade 2-propanol and special grade toluene at different ratios to a container containing the silica particles, and measuring the refractive index of the supernatant when the silica particles in the container became transparent using an Abbe refractometer.
[0076] The silica particles are preferably amorphous. In this case, silanol groups are present appropriately on the surface of the silica particles, and during the step of polishing the object to be polished, chemical interaction occurs between the silica particles and the object to be polished via the silanol groups, so that polishing proceeds well.
[0077] The fact that the silica particles are amorphous can be confirmed by the halo pattern in wide-angle X-ray scattering measurement.
[0078] The metal impurity content of the silica particles is preferably 5 ppm or less, more preferably 2 ppm or less.
[0079] When the metal impurity content of the silicon dioxide particles is 5 ppm or less, the contamination caused by the metal impurities adhering to the surface of the object to be polished is reduced during the polishing of the silicon wafer of the semiconductor device, thereby reducing the influence on the wafer characteristics. In addition, the quality degradation caused by the diffusion of metal impurities adhering to the surface of the object to be polished into the wafer is reduced, and the performance reduction of the semiconductor device manufactured from such a wafer is reduced, so it is preferred.
[0080] Moreover, when the metal impurity content of the silica particles is below 5 ppm, the changes in the chemical properties of the surface silanol groups (acidity, etc.) caused by the coordination interaction between the acidic surface silanol groups and the metal impurities and the changes in the three-dimensional environment of the silica particle surface (ease of aggregation of the silica particles, etc.) have less influence on the polishing rate, so it is preferred.
[0081] The metal impurity content of silica particles in this specification refers to the value measured by high-frequency inductively coupled plasma mass spectrometry (ICP-MS). Specifically, a silica sol containing 0.4 g of silica particles is accurately measured, sulfuric acid and hydrofluoric acid are added, heated, dissolved, evaporated, pure water is added to the remaining sulfuric acid drops to make the total amount accurately 10 g, and a test solution is prepared, and the measurement is performed using a high-frequency inductively coupled plasma mass spectrometry device. The metals of the object are set as sodium, potassium, iron, aluminum, calcium, magnesium, zinc, cobalt, chromium, copper, manganese, lead, titanium, silver, and nickel, and the total content of these metals is taken as the metal impurity content.
[0082] The metal impurity content of the silica particles can be made 5 ppm or less by obtaining the silica particles by subjecting alkoxysilane as a main raw material to a hydrolysis reaction and a condensation reaction.
[0083] In the deionization method using an alkali metal silicate such as water glass, sodium and the like derived from the raw material remain, and therefore it is extremely difficult to reduce the metal impurity content of the silica particles to 5 ppm or less.
[0084] The average primary particle size of the silica particles is preferably 10 nm to 100 nm, more preferably 15 nm to 60 nm, and further preferably 30 nm to 50 nm. When the average primary particle size of the silica particles is 10 nm or more, the storage stability of the silica sol is excellent. In addition, when the average primary particle size of the silica particles is 100 nm or less, the surface roughness and damage of the polished body represented by the silicon wafer can be reduced, and the sedimentation of the silica particles can be suppressed.
[0085] The average primary particle size of the silica particles was measured by the BET method. Specifically, the specific surface area of the silica particles was measured using an automatic specific surface area measuring device, and the average primary particle size was calculated using the following formula (2).
[0086] Average primary particle size (nm) = 6000 / (specific surface area (m 2 / g)×density(g / cm 3 ))……(2)
[0087] The average primary particle size of the silica particles can be set within a desired range depending on the production conditions of the silica particles.
[0088] The average secondary particle size of the silica particles is preferably 20nm to 200nm, more preferably 30nm to 100nm, and further preferably 55nm to 80nm. When the average secondary particle size of the silica particles is 20nm or more, the removal of particles during cleaning after grinding is excellent, and the storage stability of the silica sol is excellent. In addition, when the average secondary particle size of the silica particles is 200nm or less, the surface roughness and damage of the polished body represented by the silicon wafer during grinding can be reduced, the removal of particles during cleaning after grinding is excellent, and the sedimentation of the silica particles can be suppressed.
[0089] The average secondary particle size of the silica particles is measured by the DLS (Dynamic Light Scattering) method. Specifically, the measurement is performed using a dynamic light scattering particle size measuring apparatus.
[0090] The average secondary particle size of the silica particles can be set within a desired range depending on the production conditions of the silica particles.
[0091] The CV (coefficient of variation) value of the silica particles is preferably 10% to 50%, more preferably 15% to 40%, and further preferably 20% to 35%. When the CV value of the silica particles is 10% or more, the polishing rate of the polished body represented by silicon wafers is excellent, and the productivity of silicon wafers is excellent. In addition, when the CV value of the silica particles is 50% or less, the surface roughness and damage of the polished body represented by silicon wafers during polishing can be reduced, and the removal of particles during cleaning after polishing is excellent.
[0092] The cv value of the silica particles was calculated using the following formula (3) by measuring the average secondary particle size of the silica particles using a dynamic light scattering particle size analyzer.
[0093] cv value = (standard deviation (nm) / average secondary particle size (nm)) × 100... (3)
[0094] The association ratio of the silica particles is preferably 1.0 to 4.0, and more preferably 1.1 to 3.0. When the association ratio of the silica particles is 1.0 or more, the polishing rate of the polished body represented by the silicon wafer is excellent, and the productivity of the silicon wafer is excellent. In addition, when the association ratio of the silica particles is 4.0 or less, the surface roughness and damage of the polished body represented by the silicon wafer during polishing can be reduced, and the aggregation of the silica particles can be suppressed.
[0095] The association ratio of the silica particles was calculated using the following formula (4) from the average primary particle size measured by the above-mentioned measuring method and the average secondary particle size measured by the above-mentioned measuring method.
[0096] Association ratio = average secondary particle size / average primary particle size (4)
[0097] In view of the low content of metal impurities, excellent mechanical strength and storage stability, the silica particles of the present invention preferably have an alkoxysilane condensate as the main component, more preferably a tetraalkoxysilane condensate as the main component, and further preferably a tetramethoxysilane condensate as the main component. The main component refers to a component that is 50% by mass or more in 100% by mass of all components constituting the silica particles.
[0098] In order to obtain silica particles with alkoxysilane condensate as the main component, alkoxysilane is preferably used as the main raw material. In order to obtain silica particles with tetraalkoxysilane condensate as the main component, tetraalkoxysilane is preferably used as the main raw material. In order to obtain silica particles with tetramethoxysilane condensate as the main component, tetramethoxysilane is preferably used as the main raw material. The main raw material refers to a raw material that is 50% by mass or more in 100% by mass of all raw materials constituting the silica particles.
[0099] The surface silanol group density of the silica particles of the present invention is preferably 1 / nm 2 ~8 / nm 2 , more preferably 4 / nm 2 ~7 / nm 2 When the surface silanol group density of silica particles is 1 / nm 2 When the surface silanol group density of the silica particles is 8 / nm, the silica particles have a moderate surface repulsion and the dispersion stability of the silica sol is excellent. 2 When the silica particles have an appropriate surface repulsion, the aggregation of the silica particles can be suppressed.
[0100] The surface silanol group density of the silica particles was measured by the Sears method. Specifically, the measurement and calculation were performed under the following conditions.
[0101] Take silica sol equivalent to 1.5g of silica particles, add pure water to make the liquid volume 90mL. Under 25°C environment, add 0.1mol / L hydrochloric acid aqueous solution until the pH becomes 3.6, add 30g of sodium chloride, slowly add pure water while dissolving the sodium chloride completely, and add pure water until the total amount of the final test solution becomes 150mL to obtain the test solution.
[0102] The obtained test solution was placed in an automatic titrator, 0.1 mol / L sodium hydroxide aqueous solution was added dropwise, and the titration amount A (mL) of 0.1 mol / L sodium hydroxide aqueous solution required to change the pH from 4.0 to 9.0 was measured.
[0103] The consumption V (mL) of 0.1 mol / L sodium hydroxide aqueous solution required to change the pH from 4.0 to 9.0 per 1.5 g of silica particles was calculated using the following formula (5). The surface silanol group density ρ (number / nm) of silica particles was calculated using the following formula (6). 2 ).
[0104] V=(A×f×100×1.5) / (W×C)……(5)
[0105] A: titration amount (mL) of 0.1 mol / L sodium hydroxide aqueous solution required to change the pH from 4.0 to 9.0 per 1.5 g of silica particles.
[0106] f: titer of the 0.1 mol / L sodium hydroxide aqueous solution used.
[0107] C: Concentration of silica particles in silica sol (mass %).
[0108] W: amount of silica sol collected (g).
[0109] ρ=(B×NA) / (10 18 ×M×SBET)……(6)
[0110] B: The amount of sodium hydroxide (mol) required to change the pH from 4.0 to 9.0 per 1.5 g of silica particles calculated based on V.
[0111] NA: Avogadro constant (unit / mol).
[0112] M: amount of silica particles (1.5 g).
[0113] SBET: Specific surface area of silica particles measured when calculating the average primary particle size (m 2 / g).
[0114] (Method for producing silicon dioxide particles)
[0115] The silica particles of the present invention can be obtained by a process including subjecting tetraalkoxysilane to a hydrolysis reaction and a condensation reaction at pH 8 to 14. From the perspective of being able to easily control the hydrolysis reaction and the condensation reaction, increasing the reaction rate of the hydrolysis reaction and the condensation reaction, preventing the gelation of the dispersion of the silica particles, and obtaining silica particles with a uniform particle size, the following method is preferred: adding a solution (B) containing tetraalkoxysilane and a solution (C) added as needed to a solution (A) containing water to subject tetraalkoxysilane to a hydrolysis reaction and a condensation reaction. The average pore volume of nanoscale pores and the average pore volume of atomic-scale pores of the silica particles can be set to a desired range by the manufacturing conditions of the silica particles such as pH, reaction temperature, reaction time, catalyst concentration, and raw material supply rate; and the pressurization and heating treatment conditions such as pressurization pressure, heating temperature, and pressurization and heating time. For example, there is a tendency that the higher the reaction temperature of the hydrolysis reaction and condensation reaction of tetraalkoxysilane, and the longer the time of the hydrolysis and condensation reaction of tetraalkoxysilane, the smaller the average pore volume of the nanoscale pores of the silica particles. On the other hand, for example, there is a tendency that the shorter the reaction time of the hydrolysis reaction and condensation reaction of tetraalkoxysilane, and the higher the temperature and pressure of the pressurized heat treatment, the larger the average pore volume of the atomic-scale pores of the silica particles.
[0116] Solution (A) contains water.
[0117] The solution (A) preferably contains a solvent other than water, from the viewpoint of excellent dispersibility of the tetraalkoxysilane in the reaction solution.
[0118] As the solvent other than water in the solution (A), for example, methanol, ethanol, propanol, isopropanol, ethylene glycol, etc. can be listed. These solvents can be used alone or in combination of two or more. Among these solvents, alcohol is preferred, methanol and ethanol are more preferred, and methanol is further preferred, from the perspective of easy dissolution of tetraalkoxysilane, the solvent used in the hydrolysis reaction and the condensation reaction is the same as the solvent of the by-product, and the convenience of manufacturing is excellent.
[0119] The solution (A) preferably contains a base catalyst from the viewpoint of increasing the reaction rates of the hydrolysis reaction and the condensation reaction of the tetraalkoxysilane.
[0120] As the alkali catalyst in the solution (A), for example, ethylenediamine, diethylenetriamine, triethylenetetramine, ammonia, urea, ethanolamine, tetramethylammonium hydroxide, etc. can be listed. These alkali catalysts can be used alone or in combination of two or more. Among these alkali catalysts, ammonia is preferred from the perspectives of excellent catalytic effect, easy control of particle shape, ability to suppress the mixing of metal impurities, high volatility, and excellent removability after hydrolysis reaction and condensation reaction.
[0121] The concentration of water in solution (A) is preferably 3% to 90% by mass, more preferably 5% to 50% by mass in 100% by mass of solution (A). When the concentration of water in solution (A) is 3% by mass or more, it is easy to control the hydrolysis reaction rate of tetraalkoxysilane. In addition, when the concentration of water in solution (A) is 90% by mass or less, the reaction balance of hydrolysis reaction and condensation reaction is good, and the particle shape is easy to control.
[0122] The concentration of the alkali catalyst in the solution (A) is preferably 0.5% to 2.0% by mass, and more preferably 0.6% to 1.5% by mass in 100% by mass of the solution (A). When the concentration of the alkali catalyst in the solution (A) is 0.5% by mass or more, the aggregation of the silica particles is suppressed, and the dispersion stability of the silica particles in the dispersion is excellent. In addition, when the concentration of the alkali catalyst in the solution (A) is 2.0% by mass or less, the reaction does not proceed too quickly, and the reaction controllability is excellent.
[0123] The concentration of the solvent other than water in the solution (A) is preferably the remainder of water and the alkaline catalyst.
[0124] Solution (B) contains tetraalkoxysilane.
[0125] As the tetraalkoxysilane in the solution (B), for example, tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, tetraisopropoxysilane, etc. can be listed. These tetraalkoxysilanes can be used alone or in combination of two or more. Among these tetraalkoxysilanes, tetramethoxysilane and tetraethoxysilane are preferred, and tetramethoxysilane is more preferred, from the perspective of fast hydrolysis reaction, less residual unreacted products, excellent productivity, and easy to obtain stable silica sol.
[0126] The raw material of the silica particles may also be a raw material other than tetraalkoxysilane, such as a low condensate of tetraalkoxysilane. However, from the perspective of excellent reactivity, it is preferred that the tetraalkoxysilane accounts for 50% by mass or more and the raw material other than tetraalkoxysilane accounts for 50% by mass or less, and it is more preferred that the tetraalkoxysilane accounts for 90% by mass or more and the raw material other than tetraalkoxysilane accounts for 10% by mass or less, in 100% by mass of all the raw materials constituting the silica particles.
[0127] The solution (B) may contain only tetraalkoxysilane without a solvent, but preferably contains a solvent from the viewpoint of excellent dispersibility of the tetraalkoxysilane in the reaction liquid.
[0128] As the solvent in solution (B), for example, methanol, ethanol, propanol, isopropanol, ethylene glycol, etc. can be listed. These solvents can be used alone or in combination of two or more. Among these solvents, alcohols are preferred, methanol and ethanol are more preferred, and methanol is further preferred, from the perspective of the excellent convenience of the solvent used in the hydrolysis reaction and the condensation reaction being the same as the solvent of the by-product.
[0129] The concentration of tetraalkoxysilane in solution (B) is preferably 60% to 95% by mass, more preferably 70% to 90% by mass in 100% by mass of solution (B). When the concentration of tetraalkoxysilane in solution (B) is 60% by mass or more, the reaction solution tends to become uniform. In addition, when the concentration of tetraalkoxysilane in solution (B) is 95% by mass or less, the formation of gel can be suppressed.
[0130] The concentration of the solvent of solution (B) is preferably 5% to 40% by mass, more preferably 10% to 30% by mass in 100% by mass of solution (B). When the concentration of the solvent of solution (B) is 5% by mass or more, the formation of a gel can be suppressed. In addition, when the concentration of the solvent of solution (B) is 40% by mass or less, the reaction solution tends to become uniform.
[0131] The addition rate of solution (B) per hour relative to the volume of solution (A) is preferably 0.02 kg / hour / L to 1.3 kg / hour / L, and more preferably 0.05 kg / hour / L to 0.8 kg / hour / L. When the addition rate of solution (B) is 0.02 kg / hour / L or more, the productivity of silica particles is excellent. In addition, when the addition rate of solution (B) is 1.3 kg / hour / L or less, the formation of gel can be suppressed.
[0132] The solution (C) is a solution containing water, and preferably further contains a base catalyst.
[0133] As the base catalyst that can be contained in the solution (C), for example, ethylenediamine, diethylenetriamine, triethylenetetramine, ammonia, urea, ethanolamine, tetramethylammonium hydroxide, etc. can be listed. These base catalysts can be used alone or in combination of two or more. Among these base catalysts, ammonia is preferred from the perspectives of excellent catalytic effect, easy control of particle shape, ability to suppress the mixing of metal impurities, high volatility, and excellent removability after hydrolysis reaction and condensation reaction.
[0134] Solution (C) contains water as a solvent. For example, methanol, ethanol, propanol, isopropanol, ethylene glycol, etc. can be cited as solvents other than water. One type of solvent other than water can be used alone, or two or more types can be used in combination. Among the solvents of solution (C), it is preferred that only water or a combination of water and alcohol is used, and more preferably only water is used, from the perspective of the excellent convenience of manufacturing, since the solvent used in the hydrolysis reaction and the condensation reaction is the same as the solvent of the by-product.
[0135] The concentration of the alkali catalyst in the solution (C) is preferably 0% to 10% by mass in 100% by mass of the solution (C). The alkali catalyst in the solution (C) may also be 0% by mass, i.e., it may not contain an alkali catalyst, but in the case of containing an alkali catalyst, its concentration is preferably 0.5% by mass or more, more preferably 1% by mass or more. When the concentration of the alkali catalyst in the solution (C) is 0.5% by mass or more, it is easy to adjust the concentration of the alkali catalyst in the reaction solution from the start of the reaction to the end of the reaction. In addition, from the viewpoint of reducing the variation of the concentration of the alkali catalyst in the reaction solution, the concentration of the alkali catalyst in the solution (C) is preferably 10% by mass or less, more preferably 6% by mass or less.
[0136] The concentration of water in solution (C) is preferably 90% to 100% by mass in solution (C) 100% by mass. The concentration of water in solution (C) may also be 100% by mass, i.e., solution (C) may also be composed only of water, but in the case of including other components, the concentration of water is preferably 99.5% by mass or less, more preferably 99% by mass or less. From the viewpoint of reducing the variation of the concentration of the alkali catalyst in the reaction solution, the concentration of water in solution (C) is preferably 90% by mass or more, more preferably 94% by mass or more. In addition, when the concentration of water in solution (C) is 99.5% by mass or less, it is easy to adjust the concentration of the alkali catalyst in the reaction solution from the start of the reaction to the end of the reaction.
[0137] The concentration of the solvent other than water in the solution (C) is preferably the concentration of water and the remainder of the alkaline catalyst.
[0138] The addition of solution (B) and solution (C) is preferably carried out in the liquid of solution (A). By adding solution (B) and solution (C) to the liquid of solution (A), when it is desired to use a highly volatile alkaline catalyst represented by ammonia, and when it is desired to carry out a hydrolysis reaction and a condensation reaction at a high reaction temperature, the miscibility of each component in the reaction solution is improved, abnormal reactions in the gas can be suppressed, and the particle shape can be easily controlled. Adding to a liquid means adding below the liquid level, and by making the supply outlet of solution (B) and the supply outlet of solution (C) below the liquid level of solution (A), solution (B) and solution (C) can be added to the liquid of solution (A).
[0139] The timings of adding solution (B) and solution (C) to solution (A) may be the same or different in alternation, but are preferably the same in terms of less variation in the reaction composition and less complicated operation.
[0140] The pH in the process of hydrolyzing and condensing tetraalkoxysilane is 8.0 to 14, preferably 8.2 to 13, and more preferably 8.5 to 12. When the pH in the process is 8.0 or more, the reaction rate of the hydrolysis reaction and the condensation reaction is excellent, and the aggregation of the silica particles can be suppressed. In addition, when the pH in the process is 14 or less, the shape of the silica particles is easy to control, and the smoothness of the surface of the silica particles is excellent.
[0141] The method for manufacturing silica particles of the present invention preferably includes a step of performing a hydrolysis reaction and a condensation reaction of an alkoxysilane at 40°C or above, and more preferably includes a step of performing a hydrolysis reaction and a condensation reaction of an alkoxysilane at 46°C or above. When the reaction temperature is above 40°C, the reaction rate of the hydrolysis reaction and the condensation reaction of the alkoxysilane is moderately increased, and the four bonds of the silicon atom can form a siloxane bond before the particle growth. Thus, it is possible to suppress the alkoxy and silanol groups from remaining inside the silica particles and forming nanoscale pores, and adjust the average pore volume of the nanoscale pores of the silica particles to an appropriate range, so it is preferred. In addition, when the reaction temperature is below 50°C, the balance between the hydrolysis reaction rate and the condensation reaction rate is excellent.
[0142] The concentration of water in the reaction system of hydrolysis reaction and condensation reaction is preferably maintained at 3 mass % to 90 mass % in the total amount 100 mass % in the reaction system, more preferably maintained at 5 mass % to 30 mass %, and further preferably maintained at 6 mass % to 25 mass %. When the concentration of water in the reaction system is more than 3 mass %, it is easy to control the hydrolysis reaction speed of tetraalkoxysilane. In addition, when the concentration of water in the reaction system is below 90 mass %, the reaction balance of hydrolysis reaction and condensation reaction is good, and the particle shape is easy to control.
[0143] The concentration of the alkali catalyst in the reaction system of the hydrolysis reaction and the condensation reaction is preferably maintained at 0.5% to 2.0% by mass in the total amount 100% by mass in the reaction system, and more preferably maintained at 0.6% to 1.5% by mass. When the concentration of the alkali catalyst in the reaction system is 0.5% by mass or more, the aggregation of the silica particles is suppressed, and the dispersion stability of the silica particles in the dispersion liquid is excellent. In addition, when the concentration of the alkali catalyst in the reaction system is 2.0% by mass or less, the reaction will not proceed too quickly, and the reaction controllability is excellent.
[0144] From the viewpoint of being able to remove unnecessary components and add necessary components, the method for producing silica particles preferably further comprises the following step (1).
[0145] Step (1): A step of concentrating the obtained dispersion of silica particles and adding a dispersion medium.
[0146] The concentration of the silica particle dispersion and the addition of the dispersion medium in the step (1) may be performed first.
[0147] The method for concentrating the dispersion of silica particles is not particularly limited, and examples thereof include a heating concentration method and a membrane concentration method.
[0148] The silica particle dispersion liquid may be concentrated by the heating concentration method by heating and concentrating the dispersion liquid under normal pressure or under reduced pressure.
[0149] The dispersion of silica particles is concentrated by membrane concentration, preferably by membrane separation using ultrafiltration. Here, the main purpose of ultrafiltration is to remove unnecessary components such as intermediate products. The molecular weight cut-off of the ultrafiltration membrane used here is selected to be able to filter and separate the intermediate products in the dispersion and remove them.
[0150] Examples of the material of the ultrafiltration membrane include polysulfone, polyacrylonitrile, sintered metal, ceramic, carbon, etc. Examples of the form of the ultrafiltration membrane include a spiral type, a tubular type, and a hollow fiber type.
[0151] As the dispersion medium added to the dispersion of silica particles, for example, water, methanol, ethanol, propanol, isopropanol, ethylene glycol, etc. can be listed. These dispersion media can be used alone or in combination of two or more. Among these dispersion media, water and alcohol are preferred from the aspect of excellent affinity with silica particles, and water is more preferred.
[0152] The method for producing silica particles preferably further comprises the following step (2) from the viewpoint of increasing the condensation degree of the silica particles.
[0153] Step (2): a step of subjecting the dispersion of silica particles obtained in step (1) to a pressure-heat treatment.
[0154] The pressure of the pressurized heat treatment is preferably 0.10 MPa to 2.3 MPa, and more preferably 0.12 MPa to 2.0 MPa. When the pressure of the pressurized heat treatment is 0.10 MPa or more, the condensation degree of the silica particles can be increased. In addition, when the pressure of the pressurized heat treatment is 2.3 MPa or less, the silica particles can be produced without significantly changing the average primary particle size, the average secondary particle size, the cv value, and the association ratio, and the dispersion stability of the silica sol is excellent.
[0155] The pressure may be applied by heating the silica particle dispersion to a temperature higher than the boiling point of the dispersion medium in a sealed state. When the silica particle aqueous dispersion is heated to 100° C. or higher in a sealed state, the pressure is the saturated water vapor pressure at that temperature.
[0156] The temperature of the pressurized heat treatment is preferably 100° C. to 220° C., and more preferably 110° C. to 180° C. When the temperature of the pressurized heat treatment is 100° C. or higher, the condensation degree of the silica particles can be increased. When the temperature of the pressurized heat treatment is 220° C. or lower, the silica particles can be produced without significantly changing the average primary particle size, the average secondary particle size, the cv value, and the association ratio, and the dispersion stability of the silica sol is excellent.
[0157] The time of the pressurized heat treatment is preferably 0.25 hours to 10 hours, and more preferably 0.5 hours to 8 hours. When the time of the pressurized heat treatment is 0.25 hours or more, the condensation degree of the silica particles can be increased. When the time of the pressurized heat treatment is 10 hours or less, the silica particles can be produced without significantly changing the average primary particle size, the average secondary particle size, the cv value, and the association ratio, and the dispersion stability of the silica sol is excellent.
[0158] The pressure heat treatment is more preferably performed in an aqueous dispersion from the viewpoint of being able to increase the condensation degree of the silica particles without significantly changing the average primary particle size, average secondary particle size, cv value, and association ratio.
[0159] The pH during the pressurized heat treatment in the aqueous dispersion is preferably 6.0 to 8.0, and more preferably 6.5 to 7.8. When the pH during the pressurized heat treatment in the aqueous dispersion is 6.0 or more, the gelation of the silica sol can be suppressed. In addition, when the pH during the pressurized heat treatment in the aqueous dispersion is 8.0 or less, the condensation degree of the silica particles can be increased without significantly changing the average primary particle size, the average secondary particle size, the cv value, and the association ratio.
[0160] (Silica Sol)
[0161] The silica sol of the present invention contains the silica particles of the present invention.
[0162] The silica sol may be produced by using the dispersion of the silica particles of the present invention as it is, or by removing unnecessary components from the components in the dispersion of the silica particles of the present invention and adding necessary components.
[0163] The silica sol of the present invention preferably contains silica particles and a dispersion medium.
[0164] Examples of the dispersing medium in the silica sol include water, methanol, ethanol, propanol, isopropanol, and ethylene glycol. One of these dispersing media in the silica sol may be used alone, or two or more may be used in combination. Among these dispersing media in the silica sol, water and alcohol are preferred, and water is more preferred, from the perspective of excellent affinity with silica particles.
[0165] The content of silica particles in the silica sol is preferably 3% to 50% by mass, more preferably 4% to 40% by mass, and further preferably 5% to 30% by mass in 100% by mass of the total amount of the silica sol. When the content of silica particles in the silica sol is 3% by mass or more, the polishing rate of the polished body represented by a silicon wafer is excellent. In addition, when the content of silica particles in the silica sol is 50% by mass or less, the aggregation of silica particles in the silica sol and the polishing composition can be suppressed, and the storage stability of the silica sol and the polishing composition is excellent.
[0166] The content of the dispersion medium in the silica sol is preferably 50% to 97% by mass, more preferably 60% to 96% by mass, and further preferably 70% to 95% by mass in the total amount of the silica sol (100% by mass). When the content of the dispersion medium in the silica sol is 50% by mass or more, the aggregation of the silicon dioxide particles in the silica sol and the polishing composition can be suppressed, and the storage stability of the silica sol and the polishing composition is excellent. In addition, when the content of the dispersion medium in the silica sol is 97% by mass or less, the polishing rate of the polished body represented by the silicon wafer is excellent.
[0167] The content of the silica particles and the dispersion medium in the silica sol can be set to a desired range by removing unnecessary components from the components in the obtained silica particle dispersion and adding necessary components.
[0168] In addition to silica particles and a dispersion medium, the silica sol may contain other components such as an oxidant, a preservative, an antifungal agent, a pH adjuster, a pH buffer, a surfactant, a chelating agent, and an antibacterial and antimicrobial agent as required within a range that does not impair the performance.
[0169] In particular, from the viewpoint of excellent storage stability of silica sol, it is preferred that an antibacterial and antimicrobial agent be contained in silica sol.
[0170] As the antibacterial and antimicrobial agent, for example, hydrogen peroxide, ammonia, quaternary ammonium hydroxide, quaternary ammonium salt, ethylenediamine, glutaraldehyde, methyl p-hydroxybenzoate, sodium chlorite, etc. can be listed. These antibacterial and antimicrobial agents can be used alone or in combination of two or more. Among these antibacterial and antimicrobial agents, hydrogen peroxide is preferred from the aspect of excellent affinity with silica sol.
[0171] Antimicrobial antimicrobial agents also include substances commonly referred to as bactericides.
[0172] The content of the antibacterial and antimicrobial agent in the silica sol is preferably 0.0001% to 10% by mass, and more preferably 0.001% to 1% by mass in the total amount of 100% by mass of the silica sol. When the content of the antibacterial and antimicrobial agent in the silica sol is 0.0001% by mass or more, the storage stability of the silica sol is excellent. When the content of the antibacterial and antimicrobial agent in the silica sol is 10% by mass or less, the original performance of the silica sol will not be impaired.
[0173] The pH of the silica sol is preferably 6.0 to 8.0, more preferably 6.5 to 7.8. When the pH of the silica sol is 6.0 or more, the dispersion stability is excellent and the aggregation of the silica particles can be suppressed. In addition, when the pH of the silica sol is 8.0 or less, the dissolution of the silica particles is prevented, and the long-term storage stability is excellent.
[0174] The pH of the silica sol can be adjusted to a desired range by adding a pH adjuster.
[0175] (Abrasive composition)
[0176] The polishing composition of the present invention comprises the silica sol of the present invention.
[0177] The polishing composition of the present invention preferably contains a water-soluble polymer in addition to the silica sol of the present invention.
[0178] The water-soluble polymer improves the wettability of the polishing composition to the polished object represented by the silicon wafer. The water-soluble polymer is preferably a polymer having a functional group with high water affinity, and the functional group with high water affinity has high affinity with the surface silanol group of the silica particles, so that the silica particles and the water-soluble polymer are more closely dispersed in the polishing composition. Therefore, when the polished object represented by the silicon wafer is polished, the effects of the silica particles and the water-soluble polymer work synergistically.
[0179] Examples of the water-soluble polymer include cellulose derivatives, polyvinyl alcohol, polyvinyl pyrrolidone, copolymers having a polyvinyl pyrrolidone skeleton, and polymers having a polyoxyalkylene structure.
[0180] Examples of the cellulose derivative include hydroxyethyl cellulose, hydroxyethyl cellulose subjected to a hydrolysis treatment, hydroxypropyl cellulose, hydroxyethyl methyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose, ethyl cellulose, ethyl hydroxyethyl cellulose, and carboxymethyl cellulose.
[0181] Examples of the copolymer having a polyvinyl pyrrolidone skeleton include a graft copolymer of polyvinyl alcohol and polyvinyl pyrrolidone.
[0182] As a polymer which has a polyoxyalkylene structure, polyoxyethylene, polyoxypropylene, the copolymer of ethylene oxide and propylene oxide, etc. are mentioned, for example.
[0183] These water-soluble polymers can be used alone or in combination of two or more. Among these water-soluble polymers, cellulose derivatives are preferred, and hydroxyethyl cellulose is more preferred, from the viewpoint of high affinity with the surface silanol groups of the silica particles and synergistically exerting good hydrophilicity on the surface of the body to be ground.
[0184] The mass average molecular weight of the water-soluble polymer is preferably 1000 to 3000000, more preferably 5000 to 2000000, and further preferably 10000 to 1000000. When the mass average molecular weight of the water-soluble polymer is 1000 or more, the hydrophilicity of the polishing composition is improved. In addition, when the mass average molecular weight of the water-soluble polymer is 3000000 or less, the affinity with the silica sol is excellent, and the polishing rate of the polished body represented by the silicon wafer is excellent.
[0185] The mass average molecular weight of the water-soluble polymer was measured by size exclusion chromatography using a 0.1 mol / L NaCl solution as a mobile phase in terms of polyethylene oxide.
[0186] The content of the water-soluble polymer in the abrasive composition is preferably 0.02% to 10% by mass, more preferably 0.05% to 5% by mass, in 100% by mass of the total amount of the abrasive composition. When the content of the water-soluble polymer in the abrasive composition is 0.02% by mass or more, the hydrophilicity of the abrasive composition is improved. In addition, when the content of the water-soluble polymer in the abrasive composition is 10% by mass or less, the aggregation of the silica particles during the preparation of the abrasive composition can be suppressed.
[0187] The polishing composition of the present invention may contain, in addition to silica sol and water-soluble polymers, other ingredients such as alkaline compounds, polishing accelerators, surfactants, hydrophilic compounds, preservatives, mildew inhibitors, pH adjusters, pH buffers, surfactants, chelating agents, antibacterial and antimicrobial agents as needed, within the range that does not impair its performance.
[0188] In particular, it is preferred that the polishing composition contain a basic compound from the perspective of being able to impart a chemical action to the surface of the polished body represented by a silicon wafer to perform chemical polishing (chemical etching), and to increase the polishing rate of the polished body represented by a silicon wafer through a synergistic effect with the surface silanol groups of the silica particles.
[0189] As the basic compound, for example, organic basic compounds, alkali metal hydroxides, alkali metal bicarbonates, alkali metal carbonates, ammonia, etc. can be listed. These basic compounds can be used alone or in combination of two or more. Among these basic compounds, ammonia, tetramethylammonium hydroxide, tetraethylammonium hydroxide, ammonium bicarbonate, and ammonium carbonate are preferred, and ammonia, tetramethylammonium hydroxide, and tetraethylammonium hydroxide are more preferred, and ammonia is further preferred.
[0190] The content of the basic compound in the abrasive composition is preferably 0.001% to 5% by mass, more preferably 0.01% to 3% by mass, in 100% by mass of the total amount of the abrasive composition. When the content of the basic compound in the abrasive composition is 0.001% by mass or more, the polishing rate of the polished body represented by the silicon wafer can be increased. In addition, when the content of the basic compound in the abrasive composition is 5% by mass or less, the stability of the abrasive composition is excellent.
[0191] The pH of the polishing composition is preferably 8.0 to 12.0, more preferably 9.0 to 11.0. When the pH of the polishing composition is 8.0 or more, the aggregation of the silica particles in the polishing composition can be suppressed, and the dispersion stability of the polishing composition is excellent. In addition, when the pH of the polishing composition is 12.0 or less, the dissolution of the silica particles can be suppressed, and the stability of the polishing composition is excellent.
[0192] The pH of the polishing composition can be adjusted to a desired range by adding a pH adjuster.
[0193] The polishing composition is obtained by mixing the silica sol of the present invention, a water-soluble polymer, and other components added as needed. However, in consideration of storage and transportation, the polishing composition may be prepared at a high concentration and diluted with water or the like immediately before polishing.
[0194] (Grinding method)
[0195] The polishing method of the present invention is a method of polishing using a polishing composition containing the silica sol of the present invention.
[0196] Abrasive Composition The abrasive composition described above is preferably used.
[0197] As a specific polishing method, for example, there is mentioned a method in which the surface of a silicon wafer is pressed against a polishing pad, the polishing composition of the present invention is dropped onto the polishing pad, and the surface of the silicon wafer is polished.
[0198] (Method for manufacturing semiconductor wafer)
[0199] The method for producing a semiconductor wafer of the present invention is a method comprising the step of polishing using the polishing composition of the present invention. The specific polishing composition and polishing method are as described above.
[0200] Examples of the semiconductor wafer include a silicon wafer and a compound semiconductor wafer.
[0201] (Method for manufacturing semiconductor device)
[0202] The method for manufacturing a semiconductor device of the present invention is a method including the step of polishing using the polishing composition of the present invention. The specific polishing composition and polishing method are as described above.
[0203] (use)
[0204] The silica particles and the silica sol of the present invention can be preferably used for polishing purposes, for example, they can be used for polishing semiconductor materials such as silicon wafers, polishing electronic materials such as hard disk substrates, polishing in the planarization process when manufacturing integrated circuits (chemical mechanical polishing), polishing of synthetic quartz glass substrates used in photomasks or liquid crystals, polishing of magnetic disk substrates, etc. Among them, they can be particularly preferably used for polishing silicon wafers and chemical mechanical polishing.
[0205] As the polishing object, in addition to these, there can be listed: metals such as Si, Cu, W, Ti, Cr, Co, Zr, Hf, Mo, Ta, Ru, Au, Pt, Ag, Ni, Al, etc.; metal compounds such as oxides, nitrides, silicides, intermetallic compounds, etc. of the above metals. Among these polishing objects, metals and metal oxides can be preferably used, and metal oxides can be particularly preferably used.
[0206] As described above, the following matters are disclosed in this specification.
[0207] <1>
[0208] A silica particle, wherein the average pore volume of nanoscale pores measured by positron annihilation method is 5.3 nm 3 the following.
[0209] <2>
[0210] according to <1> The silica particles, wherein the average pore volume of nanoscale pores measured by positron annihilation method is 4.0 nm 3 the following.
[0211] <3>
[0212] according to <1> or <2> The silica particles, wherein the average pore volume of nanoscale pores measured by positron annihilation method is 1.5 nm 3 above.
[0213] <4>
[0214] according to <1> ~ <3> The silica particles according to any one of the preceding claims, wherein the average pore volume of atomic-scale pores measured by positron annihilation is 0.33 nm 3 above.
[0215] <5>
[0216] according to <1> ~ <4> The silica particles according to any one of the preceding claims, wherein the average pore volume of atomic-scale pores measured by positron annihilation is 0.80 nm 3 the following.
[0217] <6>
[0218] according to <1> ~ <5> The silica particles according to any one of the preceding claims, wherein the volume of pores having a diameter of 2 nm or less measured by a nitrogen adsorption method is 0.0070 cm 3 / g or less.
[0219] <7>
[0220] according to <1> ~ <6> The silica particles according to any one of the preceding claims, wherein the refractive index is 1.390 or more.
[0221] <8>
[0222] according to <1> ~ <7> The silica particles according to any one of the preceding claims, wherein the metal impurity content is 5 ppm or less.
[0223] <9>
[0224] according to <1> ~ <8> The silica particles according to any one of the preceding claims, wherein a tetraalkoxysilane condensate is used as a main component.
[0225] <10>
[0226] A method for producing silicon dioxide particles, comprising: <1> ~ <9> The method for producing silica particles according to any one of the preceding claims comprises the step of performing a hydrolysis reaction and a condensation reaction of alkoxysilane at 40° C. or higher.
[0227] <11>
[0228] A silica sol comprising <1> ~ <9> The silica particles described above.
[0229] <12>
[0230] A grinding composition comprising <11> The silica sol.
[0231] <13>
[0232] A grinding method, using <12> The grinding composition is ground.
[0233] <14>
[0234] A method for manufacturing a semiconductor wafer, comprising: using <12> The grinding composition is subjected to a grinding process.
[0235] <15>
[0236] A method for manufacturing a semiconductor device, comprising: using <12> The grinding composition is subjected to a grinding process.
[0237] Example
[0238] Hereinafter, the present invention will be described in more detail using Examples, but the present invention is not limited to the description of the following Examples unless it departs from the gist of the present invention.
[0239] (Measurement of the average pore volume of nanoscale pores and the average pore volume of atomic-scale pores)
[0240] Using a positron beam lifetime measurement device (National Institute of Advanced Industrial Science and Technology), a positron lifetime spectrum was obtained according to the following procedure. A dry powder of silica particles was obtained from the dispersion of silica particles obtained in the examples and comparative examples. The dry powder of silica particles was placed on a sample holder. The sample was placed under a vacuum of 4×10 -4 The dry powder of silica particles was irradiated with positrons at 20° C. and the time difference between the emission of positrons and the detection of gamma rays accompanying the annihilation of positrons was measured to obtain a positron lifetime spectrum. The incident energy of the positrons was 10 keV.
[0241] The obtained positron lifetime spectrum was fitted with the linear sum of four exponential functions to obtain the average positron lifetime of each component. The two components with short lifetimes among the four components are components that do not originate from the sample, and the one with short lifetime among the remaining two is regarded as a component originating from atomic-level pores, and the other as a component originating from the nanoscale.
[0242] The average positron lifetime was converted into an average pore volume using the following formula.
[0243] (Atomic-scale pores)
[0244] [Formula 5]
[0245]
[0246] in,
[0247] [Formula 6]
[0248]
[0249] τ is the average lifetime of positrons, R is the average radius of atomic pores, ΔR is the correction value of the radius of atomic pores, and V is the average pore volume of atomic pores.
[0250] (Nanoscale pores)
[0251] [Formula 7]
[0252]
[0253] in,
[0254] [Formula 8]
[0255]
[0256] τ is the average lifetime of positrons, R is the average radius of nanopores, r0 is the correction value of the radius of nanopores, and λ T is the annihilation rate of normal positronium in vacuum, and V is the average pore volume of nanoscale pores.
[0257] (Determination of refractive index)
[0258] The silica particles were dried powdered from the dispersions obtained in the Examples and Comparative Examples. 0.1 g of the dried silica particles was added to a 10 mL glass bottle, and the ratio of special grade 2-propanol and special grade toluene was changed. The supernatant liquid was measured when the powder in the glass bottle became transparent using an Abbe refractometer "RX-7000α" (model name, ATAGO Co., Ltd.) as the refractive index of the silica particles.
[0259] (Measurement of average primary particle size)
[0260] The dispersion of silica particles obtained in the examples and comparative examples was dried at 150°C, and the specific surface area of the silica particles was measured using an automatic specific surface area measuring device "BELSORP-MR1" (model name, Microtrac-Bel Co., Ltd.). The density was set to 2.2 g / cm using the following formula (2): 3 , calculate the average primary particle size.
[0261] Average primary particle size (nm) = 6000 / (specific surface area (m 2 / g)×density(g / cm 3 ))……(2)
[0262] (Measurement of average secondary particle size)
[0263] The average secondary particle size of the silica particle dispersions obtained in Examples and Comparative Examples was measured using a dynamic light scattering particle size analyzer "Zetasizer Nano ZS" (model name, Malvern Panalytical).
[0264] (Measurement of the volume of pores with a diameter of 2 nm or less by nitrogen adsorption method)
[0265] The dispersions of silica particles obtained in Examples and Comparative Examples were dried at 300°C, and the adsorption isotherm of nitrogen onto the silica particles was measured using a pore distribution measuring device "Nova-touch" (model name, ANTON PAAR Co., Ltd.), and analyzed using the BJH method to determine the volume of pores with a diameter of 2 nm or less.
[0266] (Mechanical Strength)
[0267] The silica particles obtained in Examples and Comparative Examples were evaluated for mechanical strength suitable for polishing a substrate having a metal oxide film on the surface using the following indices.
[0268] A: The mechanical strength is estimated to be extremely suitable for grinding.
[0269] B: Mechanical strength estimated to be suitable for grinding.
[0270] C: Mechanical strength is estimated to be unsuitable for grinding.
[0271] (Storage stability)
[0272] The storage stability of the silica particles obtained in Examples and Comparative Examples was evaluated using the following indices.
[0273] A: Presumably, the storage stability is extremely excellent.
[0274] B: Presumed to be excellent in storage stability.
[0275] C: Presumed to have poor storage stability.
[0276] [Example 1]
[0277] A solution (B) in which tetramethoxysilane and methanol were mixed at a mass ratio of 5.7:1 and a solution (C) in which a 6.6% by mass ammonia solution was prepared. A solution (A) in which methanol, pure water and ammonia were mixed in advance was charged into a reaction tank equipped with a thermometer, a stirrer, a supply pipe and a distillation line. The concentration of water in the solution (A) was set to 15% by mass, and the concentration of ammonia in the solution (A) was set to 2.4% by mass.
[0278] While maintaining the temperature of the reaction liquid at 50°C, 63.6 parts by volume of solution (B) and 24.6 parts by volume of solution (C) were added to 100 parts by volume of solution (A) at a constant rate over 153 minutes to obtain a dispersion of silica particles. Pure water was added to the obtained dispersion of silica particles to adjust the liquid volume so that the content of silica particles was about 20% by mass, while the temperature was increased to remove methanol and ammonia, to obtain a dispersion of silica particles having a content of silica particles of about 20% by mass.
[0279] [Example 2]
[0280] The dispersion of silica particles obtained in Example 1 was sealed in an autoclave, heated and maintained at 140° C. for 2 hours, thereby obtaining a dispersion of silica particles subjected to a pressure heat treatment.
[0281] [Comparative Example 1]
[0282] Commercially available silica sol (trade name "PL-3", manufactured by Fuso Chemical Industries, Ltd.) was used as it was.
[0283] [Comparative Example 2]
[0284] A solution (B) in which tetramethoxysilane and methanol were mixed at a mass ratio of 5.7:1 and a solution (C) in which a 2.9% by mass ammonia solution was prepared. A solution (A) in which methanol, pure water and ammonia were mixed in advance was charged into a reaction tank equipped with a thermometer, a stirrer, a supply pipe and a distillation line. The concentration of water in the solution (A) was set to 15% by mass, and the concentration of ammonia in the solution (A) was set to 0.52% by mass.
[0285] While maintaining the temperature of the reaction liquid at 10°C, 75.5 parts by volume of solution (B) and 27.6 parts by volume of solution (C) were added to 100 parts by volume of solution (A) at a constant rate over 612 minutes to obtain a dispersion of silica particles. Pure water was added to the obtained dispersion of silica particles to adjust the liquid volume so that the content of silica particles was about 20% by mass, while the temperature was increased to remove methanol and ammonia, to obtain a dispersion of silica particles having a content of silica particles of about 20% by mass.
[0286] The obtained dispersion of silica particles was sealed in an autoclave, and heated and maintained at 140° C. for 2 hours, thereby obtaining a dispersion of silica particles subjected to a pressure heat treatment.
[0287] Tables 1 and 2 show the evaluation results of the silica particles in the above-mentioned Examples and Comparative Examples.
[0288] [Table 1]
[0289] Table 1
[0290]
[0291] *Upper section: temperature [℃], lower section: time [h]
[0292] [Table 2]
[0293] Table 2
[0294]
[0295] According to Table 1, the silica particles obtained in Examples 1 to 2 have almost no change in particle size compared to the silica particles obtained in Comparative Examples 1 to 2, but the average pore volume of nanoscale pores is small and the refractive index is large. Since the average pore volume of nanoscale pores is within an appropriate range, it can be said that the silica particles obtained in Examples 1 to 2 inhibit the alkoxy and silanol groups from remaining inside the silica particles and forming large-volume nanoscale pores. As a result, the mechanical strength and storage stability of the silica particles obtained in Examples 1 to 2 are improved. In addition, in the process of grinding the body to be ground using the grinding composition containing the silica particles obtained in Examples 1 to 2, the silica particles are not easily destroyed.
[0296] Furthermore, as shown in Table 2, the volume of pores with a diameter of 2 nm or less of the silica obtained in Examples 1 and 2 measured by the nitrogen adsorption method is within an appropriate range. Therefore, it can also be said that the number of pores that may become the starting point of breakage is small inside the silica, and thus the mechanical strength of the silica particles of Examples 1 and 2 is improved.
[0297] Therefore, by using the silica sol and polishing composition containing the silica particles of Examples 1 to 2, the polishing object can be effectively polished without damaging it, and the silica particles can be easily removed after polishing, so that high-quality polishing products can be manufactured with good productivity.
[0298] Various embodiments have been described above, but it goes without saying that the present invention is not limited to these examples. Those skilled in the art can obviously think of various variations or modifications within the scope described in the claims, and it should be understood that these also naturally belong to the technical scope of the present invention. In addition, the various constituent elements in the above-mentioned embodiments can also be arbitrarily combined within the scope of the main purpose of the invention.
[0299] It should be noted that the present application is based on the Japanese patent application (Japanese Patent Application No. 2022-099054) filed on June 20, 2022, the contents of which are incorporated herein by reference.
[0300] Industrial Applicability
[0301] The silica particles of the present invention and the silica sol of the present invention can be preferably used for polishing purposes. For example, they can be used for polishing semiconductor materials such as silicon wafers, polishing electronic materials such as hard disk substrates, polishing in the planarization process when manufacturing integrated circuits (chemical mechanical polishing), polishing synthetic quartz glass substrates used in photomasks or liquid crystals, polishing magnetic disk substrates, etc. Among them, they can be particularly preferably used for chemical mechanical polishing of silicon wafers.
Claims
1. A silicon dioxide particle, wherein The average pore volume of nanoscale pores measured by positron annihilation is 5.3 nm 3 the following.
2. The silica particles according to claim 1, wherein The average pore volume of nanoscale pores measured by positron annihilation is 4.0 nm 3 the following.
3. The silica particles according to claim 1, wherein The average pore volume of nanoscale pores measured by positron annihilation is 1.5 nm 3 above.
4. The silica particles according to claim 1, wherein The average pore volume of atomic-scale pores measured by positron annihilation is 0.33 nm 3 above.
5. The silica particles according to claim 1, wherein The average pore volume of atomic-scale pores measured by positron annihilation is 0.80 nm 3 the following.
6. The silica particles according to claim 1, wherein The volume of pores with a diameter of less than 2 nm measured by nitrogen adsorption is 0.0070 cm 3 / g or less.
7. The silica particles according to claim 1, wherein The refractive index is 1.390 or more.
8. The silica particles according to claim 1, wherein The metal impurity content is less than 5 ppm.
9. The silica particles according to claim 1, wherein The main component is tetraalkoxysilane condensate.
10. A method for producing silicon dioxide particles, which is the method for producing silicon dioxide particles according to any one of claims 1 to 9, comprising: The step of performing the hydrolysis reaction and condensation reaction of the alkoxysilane at 40°C or higher. 11 . A silica sol comprising the silica particles according to claim 1 . 12 . An abrasive composition comprising the silica sol according to claim 11 .
13. A grinding method, comprising grinding using the grinding composition according to claim 12.
14. A method for manufacturing a semiconductor wafer, comprising: A step of polishing using the polishing composition according to claim 12.
15. A method for manufacturing a semiconductor device, comprising: A step of polishing using the polishing composition according to claim 12.
Citation Information
Patent Citations
Production of cocoon-shaped colloidal silica
JP1999060232A
Colloidal silica, silica sol, polishing composition, polishing method of silicon wafer, manufacturing method of silicon wafer, chemical mechanical polishing composition and manufacturing method of semiconductor device
JP2019089692A
Vending machine system and management server
JP2022099054A